Patients with COPD tell their stories about living with the long-term condition: an innovative and powerful way to impact primary health care professionals' attitudes and behaviour?. Issue 4 (3rd July 2016) - Foster, Faye; Piggott, Rosie; Teece, Lucy; Beech, Roger
Abstract: Background : Sub-optimal adoption of evidence based practice by primary health care professionals (PHCPs) is affecting the health of people with chronic obstructive pulmonary disease (COPD). This paper shows how 'patient stories' were used to engineer professional and organisational change. Methods : 'Stories' were transmitted via a pre-planned question and answer session involving patients and carers. The impact on PHCPs' attitudes and behaviour was explored through observing the session, open-text questionnaires completed by the PHCPs at the end of the session and clinician interviews. Findings : The stories about living with COPD, told by patients and their carers, were found to be an innovative and powerful way to impact PHCPs' attitude and behaviour. Strong motivational context was created, in which clinicians were able to see the relevance of learning through active engagement with real people. Conclusion : Long term conditions such as COPD have long term implications for the daily lives of patients and their carers. Hearing about these consequences in 'the first person' is an influential training tool with a powerful impact on PHCPs' attitudes and behaviour.